Remembrances of a UK scientist in Russia, 1966–67. (1st September 2014) - Phillips, David
David Phillips was a post-doctoral fellow on a Fulbright Scholarship at the University of Texas, Austin, where he acted as host and chauffeur to one of the IUPAC representatives, the Soviet delegate, Professor Nikolai N. Kondratiev, then Deputy Director of the Institute of Chemical Physics in Moscow. During the course of ferrying him around, Nikolai asked David about his plans after his two-year stay in Texas, David replied that he had intended to return to Europe, but was looking for one more year as a post-doctoral fellow before seeking an academic position probably back in the UK. Nikolai invited him to spend time in his Institute, and eventually, through the Royal Society/Academy of Sciences Exchange programme, this came to pass. Professor Phillips now describes his experiences, both cultural and scientific, in Russia during 1966 – 67 where he learned much about the Russian people, and also about himself. He returned with a taste for good music, Russian literature and language, and travel generally, and for taking chances in life.